PENERAPAN E-LEARNING UNTUK MENGEMBANGKAN KETERAMPILAN KOMUNIKASI DI ERA REVOLUSI INDUSTRI 4.0 PADA PERKULIAHAN IPA - Putri, Mufida Awalia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
This research aims to reveal the result of the e-learning to developing the communication skill of industry 4.0 era of students after its use in the teaching of natural science. E-learning platform that had been used was Moodle. This study was qualitative research that consisted of three stages: (1) data reduction, (2) data display, and (3) conclusion drawing / verification. The tryout subjects in this study were 36 students of Pendidikan Guru Sekolah Dasar semester 2. The data were collected by using an observation sheet to knew the indicator of communication skill, documentation, and interview. The results obtained by learning e-Learning can develop skills that must be possessed in the era of the industrial revolution 4.0. This can be seen from the communication skills of students in attending science classes. Students can articulate thoughts and ideas effectively using writing; use communication to inform something; can use e-learning media; and can communicate effectively in a variety of environments. The development of this era requires that humans have these skills to face the Industrial Revolution 4.0.Keywords: e-learning, industry revolution 4.0, natural science learning